A critical review of the paper 'The earliest datable noctilucent cloud observation (Parma, Italy, AD 1840)'. (August 2020) - Dalin, Peter
In the present critical review, my aim is to address serious calculation mistakes made by the authors. I do not want to review their interpretation of a given observation on 18 June 1840 made by Antonio Colla, who was a professor of Astronomy and Meteorology at the University of Parma. There is no sense interpreting Colla's observation since the basic astronomical calculations have been made incorrectly by the authors Chiara Bertolin and Fernando Domínguez-Castro. Summarizing, in theory and practice, astronomer Antonio Colla couldnot have observed noctilucent clouds (NLC) at Parma on 18 June 1840. That is why the conclusions of the present paper are not valid.